2016
DOI: 10.1111/and.12695
|View full text |Cite
|
Sign up to set email alerts
|

Thiol/disulphide homeostasis levels in erectile dysfunction patients

Abstract: This study explored the use of thiol/disulphide homeostasis as a novel oxidative stress marker in patients with erectile dysfunction (ED). Fifty-five patients aged 40-57 were divided into two groups: Group I (International Index of Erectile Function [IIEF-5] score between 22 and 25, n = 20) and Group II (IIEF-5 score < 22, n = 35). Blood samples were used to evaluate hormone levels, lipid profile and thiol/disulphide levels. A novel, fully automated method measured plasma native thiol, total thiol and disulphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The final value of measured TAC in the sample often depends on the procedure used in each specific assay. We measured serum FRAP as a marker of oxidative stress levels in plasma, a method commonly used for TAC measurement [7]. The results of the current study indicate that the antioxidant capacity of sera, determined as a ferric-reducing ability, is low although not significant in ED patients.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The final value of measured TAC in the sample often depends on the procedure used in each specific assay. We measured serum FRAP as a marker of oxidative stress levels in plasma, a method commonly used for TAC measurement [7]. The results of the current study indicate that the antioxidant capacity of sera, determined as a ferric-reducing ability, is low although not significant in ED patients.…”
Section: Discussionmentioning
confidence: 69%
“…Under normal physiologic conditions, cavernous endothelial cells are able to detoxify ROS by upregulating the synthesis of antioxidant enzymes when ROS production is increased [6]. Recently, an increasing number of studies have reported the role of the imbalance between the formation of ROS and antioxidant defenses in the pathogenesis of ED [7,8]. Tryptophan (Trp) is an essential amino acid required for the biosynthesis of key biosynthetic intermediates, such as the neurotransmitter serotonin, the neurohormone melatonin, and niacin.…”
Section: Introductionmentioning
confidence: 99%
“…Thiol/disulfide homeostasis is important for antioxidant defense, apoptosis, and stabilization of protein chemical structures. The excess of disulfide is related with diabetes, cardiovascular disease (28), and MetS (29)(30)(31)(32). Micoogullari et al reported that thiol/ disulfide homeostasis is altered also in ED, and this may be a factor in its pathophysiology.…”
Section: Discussionmentioning
confidence: 99%